Reflections on La Esperanza - Anita Cortez (Educational Considerations, 2007)
It is Christmastime. My birthday is three days away, and I will be 56. There is the ugliest cup on campus sitting on my desk. What does it all mean?
Keywords: undergraduate; research; program; vocabulary; Kansas; reflections; La Esperanza